Fates of the components in cotton stalk during the hydrothermal oxidative pretreatment and its relationship with the upgrading of biochar pellets and wood vinegar. (15th July 2022) - Xu, Jiaqing; Zhang, Shouyu; Zhang, Peizheng; Shi, Yue; Huang, Dongdong; Lin, Chunyu; Wu, Yuxin
Highlights: Change of the components in CS after HO pretreatment is quantitatively measured. HO pretreatment improves the quality of biochar pellets and wood vinegar. The enrichment of hemicellulose and cellulose conrtibutes to the upgrading effect. Pretreatment at 180 °C is best for CS to produce biochar pellets and wood vinegar. Abstract: In the present study, biochar pellets and wood vinegar are prepared from the cotton stalk (CS) through the densification and pyrolysis, and hydrothermal oxidative (HO) pretreatment (160–260 °C) is conducted to CS to upgrade the quality of biochar pellet and wood vinegar (WV). The results show that HO pretreatment can decompose the hemicellulose, amorphous cellulose, crystalline cellulose, and lignin at 160–230 °C, 160–200 °C, 200–260 °C, and < 200 °C, respectively. Therefore, the hemicellulose and cellulose (especially the crystalline cellulose) in CS are enriched at 160–180 °C and 160–200 °C respectively. Due to the enrichment of hemicellulose and cellulose, the organic compounds in WV increase dramatically after HO pretreatment, resulting in a significant increase in the density and acidity of WV. Furthermore, due to the enrichment of hemicellulose and cellulose, the biochar pellets exhibit more densified internal structures after HO pretreatment, contributing to a higher relaxation density, energy density, and compressive strength. Moreover, the biochar pellets exhibit better combustion performance and lower ash content after HO pretreatment at 160–180 °C. The CS sample pretreated at 180 °C is the best material for the production of biochar pellets and WV.